Efectos psicológicos del proyecto de memoria histórica La guerra que no hemos visto (2017)
ABSTRACT: The article presents the results of the research “Psychological effects of the historical memory project The war we have not seen” done during 2016 and approved by eafit University. Through a case study and a triangulation of interviews, the narratives of seven participants are analyzed about their link with the project before, during and after being in contact with it. Three concepts that account for the context of the project are addressed: representations of the armed conflict, ‘gray zone’ and memory. It also delves into the psychological effects found: transformation, humanization, resignification processes, trust and forgiveness. Finally, the article presents the importance of this project and the way it contributes to reparation in the colombian conflict and transitional justice.